Architecture System Root and the Tensile Strength of Piper sarmentosum and Pandanus amaryllifolius for Application in Biotechnology on Land Slope Tropical - Yahya Rizki Abdillah; Taufiq Caesar Hidayat; Intan Nadhirah Masri (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Erosion and slope instability are major causes of land degradation in tropical areas. This research aims to evaluate the root architecture and tensile strength of Piper sarmentosum (Kaduk) and Pandanus amaryllifolius (Pandan) as candidate vegetation for slope stabilization using biotechnology. Root samples were analyzed using the WinRHIZO software to characterize root morphology, while tensile strength was tested with a digital push-pull meter (AMF-300) using the equation σ = 4F/πd². The results show significant differences between the two species. Kaduk has a fibrous root system (type H) with an average fine root diameter of 0.65 ± 0.02 mm and a length-to-volume ratio of 600.38 ± 384.87 cm/m³, which effectively increases soil surface cohesion. Pandan has a very thick adventitious root system (type VH) with an average root diameter of 3.74 ± 0.53 mm and a large surface area of 155.75 ± 0.22 cm², functioning as a strong anchor to stabilize lower soil layers. Both species exhibit a strong correlation between root diameter and tensile strength, with Kaduk showing higher tensile stress (R² = 0.8652) and Pandan demonstrating greater total withdrawal force. The excellent results indicate that combining these two species can double slope stability compared to using either species alone, making this an effective and sustainable vegetative solution for tropical land management. It is recommended to plant Kaduk on the upper slope to strengthen the soil surface and Pandan in the middle to lower slope sections to serve as a structural anchor, thereby optimizing the natural erosion-retention system.